التراث الشعبي ، سجالات التناول ، الوظيفة و التنمية - عبد الرزاق, عريف (Sciences de l'Homme et de la Société; Vol. 5 (2013): SCIENCES DE L'HOMME ET DE LA SOCIÉTÉ, 2012)
يحاول  هذا  المقال أن  يبحث في  مجال من  المسكوت  عنه – إلى حد  ما- في العلوم الاجتماعية و هو التراث الشعبي و أن  يستوضح  حقيقته  داخل  البناء  الاجتماعي هل هو  راسب ثقافي تخلف من عصور  اجتماعية سابقة، وبالتالي وجوده الآن ليس سوى وجودا  شكليا أم أنه عنصر  فاعل مبثوث في مكونات البناء  الاجتماعي  و  يرتقي بوجوده إلى مرتبة  الوظيفي ؟   This paper tries, to search in a field of an untold story ( to some extent ) in sociology: that of popular heritage, and, to clarify its reality within social structure : is it a cultural residuum lagging from previous social eras, and whose existence today is therefore only a formal existence?, or is it an effective actor transmitted within the social structure and amounts to the rank of a function?.